Respuesta :

Answer: The answer is (A) 22+(-22)+(-10).


Step-by-step explanation:  The given expression is 22+(-32). Its value is     22-32 = -10.

(A) The value of first expression is 22+(-22)+(-10) = 22-22-10 = -10.

(B) The value of second expression is 22+(22)+(-10) = 22+22-10 = 34 ≠ -10.

(C) The value of third expression is 22+(-22)+(10) = 22-22+10 = 10 ≠ -10.

(D) The value of fourth and last expression is 22+0+32 = 54 ≠ -10.

Since the value of the given expression matches with the first option, so the correct option is (A).


Answer:

Option A.

Step-by-step explanation:

The given expression is

[tex]22+(-32)[/tex]

Simplify this expression.

[tex]22-32[/tex]

[tex]-10[/tex]

Let as consider given options are

A. 22 + (–22) + (–10)

B. 22 + (22) + (–10)

C. 22 + (–22) + (10)

D. 22 + 0 + 32

Simplify each expression.

A. 22 + (–22) + (–10)  = -10

B. 22 + (22) + (–10)  = 34

C. 22 + (–22) + (10)  = 10

D. 22 + 0 + 32 = 54

Expression A has the same value as the given expression.

Therefore, the correct option is A.